(untitled) (IIUC Studies, 2012)
In this essay, firstly, I will discuss importance of rating scales, relationship between assessment criteria and operations and conditions and effectiveness of rating scales while assessing writing. Secondly, I will examine a selection of scales and subsequently there will be an estimation of those in meeting objectives of the tests and of the course. Finally, I will recommend a suitable rating scale to test English First paper and English Second Paper writing skill at HSC level in Bangladesh evaluating the existing one where I will mention steps to be taken to reduce inter and intra- rating fluctuation in scoring. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12247 IIUC Studies Vol.6 2010: 35-52